A rare case report of large bilateral vulval elephantiasis - Kaur, Manmeet; Malik, Renuka; Datta, Kamna; Khera, Kaveri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Elephantiasis, the result of chronic lymphedema, is characterized by gross enlargement of the limbs or genitalia. It occurs because of obstructive diseases of the lymphatic system. Genital elephantiasis is a common result of filariasis. Other causes are lymphogranuloma venereum. granuloma inguinale, carcinomas, lymph node dissection, irradiation and tuberculosis. Filarial elephantiasis of the female genitalia is extremely uncommon, about 1-2% of the total cases of filarial elephantiasis. Mrs. X, 25 years old female, P1L1, resident of a village in Bihar presented to gynaecology OPD of ABVIMS and Dr. RML Hospital on 06th January 2020 with complaint of huge progressively increasing vulval swelling since 3 years. Patient had come from Bihar for treatment. She had been showing in her native place for 2 years but now the lump had made her walking difficult. She did not give history of any drug given for treatment for filariasis. She gave history of being treated for pulmonary Koch 10 years back. On examination, there was a non- ulcerative, polypoidal growth of around 20×14×11 cm arising from bilateral labia majora and minora obstructing the vulval cleft. There was no associated lymphadenopathy or limb oedema. All the investigations were within normal limits. Microfilaria antigen testing done at night was negative. Patient was given diethylcarbamazine and excision of the lump was done on 14th February 2020. Histopathological report showed dilated lymphatics with non-caseating granulomas, consistent with filariasis. In endemic countries like India, filariasis is the commonest cause of elephantiasis; however genital filariasis in woman is very rare. Other cause could be tuberculosis which is still rarer. Early diagnosis and treatment of filariasis can eradicate this neglected tropical disease which causes disfigurement and severe morbidity as its sequelae.